IMPROVING THE MORAL EDUCATION OF CHILDREN WITH DEVIANT BEHAVIOR - Ergasheva Oyjamol Jakhongirovna, Toshboyeva Farida Abdukhalilovna (Journals Park Publishing, 2022)
There is a direct relationship between the development of deviant behavior among the younger generation and the growth of criminal phenomena in society. The desire to commit illegal actions is increasing with the development of deviant behavior of children and adolescents. Therefore, preventive work should be introduced everywhere in all educational institutions. Their goal is to teach adolescents that every action must be responsible. Behavior that does not correspond to the understanding of most people is called deviant. Distracting behavior does not include the usual actions of the average citizen, since they do not cause misunderstanding, admiration, admiration, fear, enmity on the part of ordinary citizens. In this article, opinions and considerations are made about improving the moral education of children with Deviant behavior.
Keywords: Deviant, deviation, prevention, behavior criterion, various alien ideas, bad behavior, negative habits, suicide, puberty.